2021
DOI: 10.1161/strokeaha.121.034049
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided BoNT-A (Botulinum Toxin A) Injection Into the Subscapularis for Hemiplegic Shoulder Pain: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background and Purpose: This study aimed to assess the efficacy of an ultrasound-guided lateral approach for BoNT-A (botulinum toxin A) injections into the subscapularis in patients with hemiplegic shoulder pain. Methods: This single-center trial used a randomized, double-blind, placebo-controlled design. The key inclusion criteria were a visual analog scale score of ≥4 cm and a modified Ashworth scale score of ≥1+. The patients were randomized to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 38 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…To aid the injection of BoNT-A, patient positioning is important. Although unassisted injection of superficial shoulder muscles can be done in practice using anatomical landmarks, guided techniques are particularly recommended for this muscle group due to the difficulty of accurate injection, particularly in deeper muscles ( 31 ) and in trunk muscles for risk of penetration into deeper structures like the pleura.…”
Section: Resultsmentioning
confidence: 99%
“…To aid the injection of BoNT-A, patient positioning is important. Although unassisted injection of superficial shoulder muscles can be done in practice using anatomical landmarks, guided techniques are particularly recommended for this muscle group due to the difficulty of accurate injection, particularly in deeper muscles ( 31 ) and in trunk muscles for risk of penetration into deeper structures like the pleura.…”
Section: Resultsmentioning
confidence: 99%
“…For example, our participants injected subscapularis and latissimus dorsi in similar frequencies, while Nalysnk et al found that the subscapularis was injected 1.9 times more than latissimus dorsi. Emerging RCTs have shown that BoNT-A injections into the subscapularis have shown improvements in spasticity, range of motion and pain of the shoulder [ 13 ]. The reason for this variability is potentially related to the on-label indications of the individual BoNT-A product monographs where the shoulder girdle muscles are not indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Canadian Stroke Best Practice Guidelines state that the use of BoNT-A for upper limb spasticity to increase range of motion and decrease pain is supported by Level B evidence in less than 6 months post-stroke and Level A evidence more than 6 months post-stroke [ 10 ]. Multiple randomized controlled trials have studied the use of BoNT-A in the shoulder girdle muscles for post-stroke spasticity [ 11 , 12 , 13 , 14 ] and there is conflicting evidence on its efficacy, likely related to variability in muscles, doses, and dilutions injected. There are currently no publications that describe how Canadian physicians currently use BoNT-A to treat spasticity of the shoulder muscles.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that patients require a 1.4-cm reduction in the VAS pain score to achieve a minimal clinically important difference ( 42 ). In addition, the treatment was considered to have yielded good results when the patient's VAS score was <3.33 cm (i.e., mild pain) or when the score was less than half of the initial score ( 43 ). The secondary endpoints were disability and ADL, measured by the pain-free passive range of motion (PROM) of the shoulder, the upper extremity Fugl-Meyer Assessment (FMA,) and Modified Barthel Index (MBI).…”
Section: Methodsmentioning
confidence: 99%